(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article discusses the emergence and development of linguoculturology as a scientific field. It examines the interrelation of language, culture, and human cognition, focusing on how national mentality and cultural values are expressed through language. Key research trends in global and Uzbek linguistics are analyzed, with particular attention given to the lack of linguoculturological studies on historical-literary texts and the potential research directions in this area.